ANALISIS KEMAMPUAN MEMBACA AL-QUR’AN PADA SISWA MTS JAMSAREN KELAS VIIIC - Lutfianto, Ifan; Faza Octavio Abdi Robbil Ka’bah; Riki Adiyanto; Muhammad Rohadi; Andi Setiawan (CV. Kalimasada Group, 2025)
This study aims to analyze the Qur'anic reading ability of Grade VIIIC students at MTs Jamsaren using a descriptive qualitative method. The main focus is to gain an in-depth understanding of the factors influencing students' Qur'anic reading skills, such as learning experiences, social environment, and student motivation. Data were collected through oral tests, direct observations, and interviews with students and teachers. The analysis revealed varying levels of reading proficiency, influenced by students' understanding of tajwid, phonetic skills, and practice frequency. These findings provide a clear picture of common difficulties faced by students and the strategies used to overcome them. This study is expected to serve as a foundation for developing more effective Qur'anic learning strategies and as a reference for further research in similar Islamic education contexts.